ROLE OF AHARAPARINAMKARA BHAVA IN DIGESTION – AN APPLIED - Sampada S. Sant; Shilpa K. Ingle; K.R.Ugale (International Journal of Applied Ayurved Research, 2020)
Different factors affecting digestion are described in Ayurveda. One of them is principle factor and others are supporting ones. This process is known as aharaparinaman that means “ultimate fate of eaten food, facilitation of health and different problems of health resembles with this. If food is as per requisites of body entities “ultimate fate of food” facilitates health. Otherwise eaten food could be problematic to health. This law is stated by charak Samhita in sharirsthan 6th chapter, where parinamana biotransformation process is explained. Ingested food is biotransformed into body entities. If food bears qualities facilitating body entities, it is able to nourish and replenish these body entities. If food bears qualities opposite to body, such food keeps these body entities ill nourished. So, factors which make food to undergo “ultimate fate” are called “aharaparinamakara bhava.” These are ushma, vayu, kleda, Sneha, kala and samayoga. Everyone of them are having its own specific action.